STRATEGI PEMBELAJARAN DALAM MENINGKATKAN HASIL BELAJAR PENDIDIKAN AGAMA ISLAM - Ridma Diana (Jurnal Tarbiyah Jamiat Kheir, 2023)
This article aims to descriptively analyze how the learning strategies carried out by Islamic Religious Education teachers strive to improve learning outcomes in the field of Islamic Religious Education. The method used in this writing is a qualitative method with a type of literature review approach (study literature). Some of the references and guidelines for writing come from primary sources and secondary sources taken from several relevant previous studies, books, and reputable journals. Data collection in this article is done by documentation and data analysis using content analysis. The results of the analysis in this study explain that the learning strategy of Islamic Religious Education teachers in Islamic Religious Education subjects or fields of study can use several types of methods in learning activities. The strategy is at the stage of conceptualizing in a planned manner by looking at the characteristics of learning for the implementation of learning. While the method is at the implementation stage to be actualized by Islamic Religious Education teachers in the process of learning activities and Islamic Religious Education teachers can choose learning methods to improve Islamic Religious Education learning outcomes such as exemplary attitudes, lectures, questions and answers, demonstrations and discussions. Keywords: Teaching and learning strategies; Learning outcomes; Islamic Religious Education